2022
DOI: 10.1002/cam4.4552
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive profiling of the TRIpartite motif family to identify pivot genes in hepatocellular carcinoma

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 62 publications
(166 reference statements)
0
3
0
Order By: Relevance
“…Besides, bioinformatic mining revealed that TRIM28, TRIM37, TRIM45, and TRIM59 could serve as efficient biomarkers in predicting OS, PFS, DSS, and RFS based on TCGA [ 63 , 64 ]. Another study built a TRIM gene-based signature (including TRIM5, MID1(TRIM18), TRIM21, TRIM32, TRIM44, and TRIM47), which shows decent efficiency in predicting OS [HR: 6.630 (3.030–14.504), p < 0.001] in TCGA and GSE76427.…”
Section: Expression Pattern and Biological Functions Of Trim Proteins...mentioning
confidence: 99%
“…Besides, bioinformatic mining revealed that TRIM28, TRIM37, TRIM45, and TRIM59 could serve as efficient biomarkers in predicting OS, PFS, DSS, and RFS based on TCGA [ 63 , 64 ]. Another study built a TRIM gene-based signature (including TRIM5, MID1(TRIM18), TRIM21, TRIM32, TRIM44, and TRIM47), which shows decent efficiency in predicting OS [HR: 6.630 (3.030–14.504), p < 0.001] in TCGA and GSE76427.…”
Section: Expression Pattern and Biological Functions Of Trim Proteins...mentioning
confidence: 99%
“…AML TRIM62 [23] / HCC TRIM26 [24], TRIM28, TRIM37, TRIM45, TRIM59 [25], TRIM59 [26] TRIM11 [27,28], TRIM16 [29], TRIM24 [30], TRIM25 [31], TRIM27 [32], TRIM31 [33], TRIM37 [34], TRIM50 [26], TRIM3, TRIM5, TRIM21, TRIM27, TRIM32, TRIM44, TRIM47, TRIM72 [35] RCC / TRIM27 [36], TRIM37 [37], TRIM44 [38] UCB / TRIM65 [39] GBC TRIM31 [40] PTC / TRIM14 [41] HEC / TRIM44 [42] TGCT / TRIM44 [43] NPC / TRIM11 [44] OC TRIM50 [45] TRIM59 [46] CRC TRIM1, TRIM2, TRIM6, TRIM13, TRIM26, TRIM35,TRIM55 [47], TRIM58 [48] TRIM23 [49], TRIM24 [50], TRIM27 [51], TRIM47 [47], TRIM39 [52] Pancreatic carcinoma TRIM36 [53], TRIM50 [54] TRIM11 [55], TRIM15 [56], TRIM37 [57], TRIM47 [58], TRIM59 [59] Gastric carcinoma TRIM3 [60], TRIM21 [61] TRIM14 [62], TRIM15 [63], TRIM23 [64], TRIM29 [65], TRIM32…”
Section: Cancer Type Low Expression Level High Expression Levelmentioning
confidence: 99%
“…The extent of ubiquitination is determined by the concerted actions of ubiquitinases and deubiquitinases. In this regard, tripartite motif-containing (TRIM-containing) proteins comprise a large family of RING domain-containing E3 ubiquitin ligases that regulate inflammation, immunity, fibrosis, and cancer (11)(12)(13)(14). However, only a few members of the TRIM family have been investigated in the context of metabolic disorders thus far.…”
Section: Introductionmentioning
confidence: 99%